1993
DOI: 10.1017/s0272263100011943
|View full text |Cite
|
Sign up to set email alerts
|

Input Enhancement in Instructed SLA

Abstract: The concept of input to the language learner is examined with reference to some current theorizing about language processing and the idea of modular systems of knowledge. The question of what this can tell us about the actions taken by teachers and textbook writers is addressed specifically with regard to manipulating, or "enhancing," the input ideally so that it will affect learner knowledge and thereby learner behavior. The logic of the argumentation is that, in exposing the learner to the second language, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
257
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(282 citation statements)
references
References 13 publications
7
257
0
5
Order By: Relevance
“…One of the issues in L2 acquisition research has been whether awareness can lead to actual L2 acquisition and production. On the one hand, researchers such as Smith (1993), Truscott (1998), and Judd (1999) argue that knowing an L2 feature or having awareness of it does not necessarily mean one can acquire or use that L2 feature efficiently. On the other hand, researchers such as Schmidt and Frota (1986), Fotos (1993), and Narita (2012) have shown a positive relationship between noticing L2 features and their emergence in learners' later L2 output.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the issues in L2 acquisition research has been whether awareness can lead to actual L2 acquisition and production. On the one hand, researchers such as Smith (1993), Truscott (1998), and Judd (1999) argue that knowing an L2 feature or having awareness of it does not necessarily mean one can acquire or use that L2 feature efficiently. On the other hand, researchers such as Schmidt and Frota (1986), Fotos (1993), and Narita (2012) have shown a positive relationship between noticing L2 features and their emergence in learners' later L2 output.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for exploring the effect of teaching on learners' pragmatic development, as Rose (2005) notes, has been underscored by Noticing Hypothesis (Schmidt, 1990), contending that simple exposure to the target language is not enough since there are pragmatic functions and relevant contextual factors which are often not salient to learners and so less likely to be noticed even after exposure for a long period of time. Unlike Krashen (1985) and Reber (1989) who claim that unconscious learning processes are better than conscious ones and are responsible for most L2 production, some other second language acquisition researchers argue that making certain forms noticeable through consciousness raising (CR) and drawing learners' attention to these forms can help learners in the language acquisition process (R. Ellis, 1995;Rod Ellis, 2008;Schmidt, 1990Schmidt, , 1993aSchmidt, , 1993bSchmidt, , 1995Schmidt, , 2001Schmidt, , 2012Smith, 1993). In earlier research on CR, the focus was on grammar instruction and learning (Fotos, 1993(Fotos, , 1994Smith, 1993), while Rose (1994) proposed pragmatic consciousness raising (PCR) as an important approach towards teaching pragmatics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Input enhancement (and input flooding as one of its versions) is Sharwood Smith's (1993) expression for referring to any pedagogical technique that teachers use to make specific features in the input more salient because noticing the input facilitates its learning (Schmidt, 1990). However, the findings in the domain of input enhancement are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers believe that students must notice a grammatical feature in order for it to be learned, no matter how often an instructor attempts to teach it explicitly (Ellis, 1993;Schmidt & Frota, 1986;Sharwood Smith, 1993;Stevick, 1996); however, several support the integration of explicit grammar teaching in world language classroom lessons. Fotos (1993) and Fotos and Ellis (1991) have shown that conscious-raising tasks, created by teachers in which students figure out linguistic rules by working interactively in small groups to solve grammar problems in the world language, can aid in the development of students" grammatical competence.…”
Section: B Deep Structurementioning
confidence: 99%